THE MATERNAL, SANITATION, CHILD’S INFECTIOUS DISEASE HISTORY AND DIARRHEA AMONG UNDER 5 AGE CHILDREN IN SAMPANG - Ernia Haris Himawati; Laila Fitria (Jurnal Riset Kesehatan, 2020)
Diarrhea is the second leading cause of children death in the world after pneumonia. The case managements have been increased and developed but the mortality rate due to diarrhea is still high. Sub-Saharan Africa and Southeast Asia were known as the highest case regions of diarrhea, including Indonesia as part of the developing countries. The purpose of this study was to analyze the relationship between maternal factors, sanitation, and a history of childhood infectious diseases with the incidence of diarrhea in Sampang. The research used a cross-sectional design study with a total sampling technique. The source data was from Riskesdas 2018  by Indonesian Health Ministry and analyzed by univariate, bivariate, and multivariate. The result of multivariable logistic regression analysis showed that maternal factors: handwashing behavior   (OR 4.687; 95% CI 0.473-46.469); education level (OR 1.815; 95% CI 0.108-1177), waste management (OR 4.333; 95% CI 0.509-36.011) and a history of infectious disease in children (OR 5.421; 95% CI 1.444 -20.354).